PENGEMBANGAN MEDIA PEMBELAJARAN BOX BERHITUNG TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS 1 SD - Mazidaturrahmah Aprilia; Satrio Wibowo; Galuh Kartika Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research develops a Box Counting learning media that aims to improve the mathematics learning outcomes of grade 1 elementary school students.The research method used is the research and development method or Research and Development with the Analys, Design, Development, Implementation, dan Evaluation (ADDIE) development model. The research subjects were media experts, material experts, and students. The research instruments were validation, tests and student response questionnaires. The results of the development in the form of counting box learning media on mathematics learning outcomes of grade I elementary school students, based on the results of the media expert assessment received a score of 93.5%